(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of bacterial isolates in blood culture among patients with acute pyogenic meningitis. Study Design: Descriptive / cross-sectional study Place and Duration of Study: This study was conducted at the Department of Medicine, Qazi Hussain Ahmad Medical Complex, Nowshera from November, 2017 to May, 2018. Materials and Methods: A total of 193 patients using 43.4% proportion of positive blood culture with acute bacterial meningitis, 95% confidence level and 5% margin of error, using WHO software, presenting features of pyogenic meningitis were included in the study and subjected to blood culture to record the findings. Results: The mean age group of our sample was 32.4 + 10.9 years of which 66.8% male patients and 33.2% female patients. Most of the patients i.e. 59.6% were in the age group up to 35.00 years. Positive blood culture was seen in 60.1% of cases with E Coli being the most frequent in 25% of patients followed by Pneumococcus in 22.4% of patients, Meningococcus in 21.6% of patients, Klebsiella in 9.5% and H. Influenza in 8.6%. Conclusion: Acute pyogenic meningitis is a common occurrence in our population with E. Coli, Pneumococci and Meningococci being the common culprits.